HUBUNGAN DAYA TERIMA MAKANAN DAN ASUPAN GIZI DENGAN Z-SKOR INDEKS MASSA TUBUH BERDASARKAN UMUR PADA SANTRI PUTRI (STUDI DI PONDOK PESANTREN MODERN ISLAM ASSALAM SUKOHARJO) - Budiman, Delima Siskawati; Suyatno, Suyatno; Pangestuti, Dina Rahayuning (Jurnal Kesehatan Masyarakat (e-Journal), 2020)
The nutritional status of adolescent who live in Islamic boarding schools on average is lacking. Poor nutritional status can be directly influenced by food intake and food acceptability. The implementation of food in Islamic boarding school is a benchmark for the achievement of good nutritional status. The purpose of this research is  to determine the relation of food acceptability and nutritional intake with the nutritional status of female students in Modern Islamic Boarding Schools Assalam Sukoharjo. The study used a cross-sectional design and the sampling used simple random sampling techniques. Sample total was 45 students. The independent variable and the dependent variable were analyzed by using correlation test. Descriptive analysis results shown 68.9% of students had less acceptance, 91.1% of students had energy intake that is classified as severe deficit and 66.7% of students had protein intake that is classified as over. The result showed that there is no relation between food acceptability (p = 0.690), energy intake (p = 0.629), and protein intake (p = 0.985) with nutritional status. The result shown that the nutritional status of a person who live in a boarding school was not influenced by food acceptability and nutritional intake but the presence of other factors such as body image (p = 0.007), appetite (p = 0.026), and outside food (0.019). Food providers at the Islamic boarding school should  pay attention to the variety of food processing that will be served to student so that student do not feel bored and the importance of providing education related to proper dieting methods to maintain optimal nutritional status